Basal values, intra-day and inter-day variations in tear film osmolarity and tear fluorescein clearance. (July 2014) - García, Noelia; Tesón, Marisa; Enríquez-de-Salamanca, Amalia; Mena, Laura; Sacristán, Amelia; Fernández, Itziar; Calonge, Margarita; González-García, María J.
Abstract Purpose: The aim of this study was to determine the normal inter-day and intra-day variations in tear film osmolarity and the tear fluorescein clearance test (T-FCT) in healthy subjects. Methods: Tear samples from 24 young, healthy adults were collected from 11:00 AM to 1:00 PM (midday) and 5:00 PM to 7:00 PM (evening) on three non-consecutive days. Tear osmolarity measurement and the T-FCT were performed to assess the basal values and inter-day and intra-day variations of the test results. A freezing point depression osmometer was used to analyze the tear osmolarity, and the T-FCT was performed using a fluorophotometer. Results: The mean osmolarity value was 270 ± 4.4 mOsm/l and the mean T-FCT result was 2.97 ± 0.17 fluorescence arbitrary units. The inter-day or intra-day tear osmolarity values did not differ significantly. The T-FCT results varied significantly during the day, with significantly (p = 0.0004) higher results in the evening; no significant differences were found in the inter-day analysis. Conclusions: Tear osmolarity was unaffected by intra-day variations; however, the T-FCT showed an inter-day variation, which indicated that the time of day when the test is performed must be considered when it is used to evaluate the diagnosis of dry eye disease, disease progression or therapeutic effectiveness.